Desempenho, anatomopatologia dos sistemas digestório e reprodutor de codornas japonesas em postura, alimentadas com dieta contendo óleos essenciais - Fernandes, Joelly Mariano Barbosa (2018)
Performance, anatomopatology of systems digestory and reproductive of quais japaneses in posture feeded with diet containing essential oils 2018. Dissertation (Master in Veterinary Sciences) - Center of Agrarian Sciences and Engineering, Federal University of Espírito Santo, Alegre, ES, 2017. The objective was to verify the effect of essential oils used as a natural alternative in the control grain pests stored on the performance and intestinal morphology and reproductive system of Japanese laying quails fed with a diet containing such oils. We used Five essential oils (Pimenta Preta, Pinho, Ginger, Capim Limão and Alecrim) more a control group (only feed), diluted in 1% solution and incorporated into the ration at a ratio of 3% to the total food, being six treatments with six replicates, constituting 36 experimental units, each with eight Japanese quails evenly distributed according to weight and posture. The basal diet was formulated based on soybea and corn. The duration of the experimental period was 42 days. 36 animals were euthanized, one animal per experimental unit. The variables analyzed were posture rate, ration consumption, morphology of the duodenum, pâncreas, jejunum, ileum, cecum, infundibulum, magnum, isthmus, uterus, and duodenal morphometry. The lowest posture rate was presented for T3, T4 and T5, however, they were similar to the control. There was no difference in the feed intake of the animals. In the duodenum all treatments presented congestion, with T2 having the lowest indexes, and T6 was the treatment that did not present inflammation. In the jejunum, T6 had the largest number of animals with alterations - congestion, hemorrhage and inflammation. T1, T4 and T5 had the highest percentage of animals without alterations. In the ileum, T6 had a higher index of animals with congestion, and T4 and T5 had more animals without alterations. In the cecum all treatments that used essential oil in the diet presented 50% of the animals without alterations, whereas in the T6 they were only 16.66%. In the pancreas all T6 animals presented congestion and the least presented was T2. In the infundibulum, T4 presented fewer alterations, and T2 presented the most changes. In the magnum, T2 presented animals with hemorrhage and T1 presented the highest amount of intense congestion. In the isthmus, all treatments presented congestion, with T1 presenting the lowest rates and T3, as well as hemorrhage in the infundibulum. In the uterus, T1 presented less severe alterations, and in contrast, T3 presented the most severe alterations. The largest intestinal villi were described in T6, which was similar to T1, T3 and T5. The use of essential oils in quail feed did not modify the organoleptic characteristics of the ration, since there was no statistical difference in the amount of feed consumed. As to the posture, the oil of pine and black pepper were beneficial to the birds and served as stimulus to the production in relation to the other three treatments with oils. The essential oils can affect histological parameters of Japanese quail and promote anti-inflammatory action, mainly on the cecum, pancreas, isthmus and magno. In the morphometric analysis of the duodenum, the oils of black pepper, ginger and lemon grass were beneficial to intestinal villi compared to ginger and pine oils